Dedifferentiated melanomas: Morpho-phenotypic profile, genetic reprogramming and clinical implications - Massi, Daniela; Mihic-Probst, Daniela; Schadendorf, Dirk; Dummer, Reinhard; Mandalà, Mario (Cancer treatment reviews, 2020)
•Dedifferentiated melanomas pose diagnostic interpretative challenges.•Dedifferentiation underlies the phenotypic and genetic plasticity of melanoma.•Melanoma cells can shift through different transcriptional programs of differentiation.•Dedifferentiation is a mechanism of resistance to immunotherapy and targeted therapy. Phenotypic plasticity of malignant melanoma is a well-known phenomenon. Several translational studies and small case series have reported this clinical and biological entity, particularly in metastatic melanoma, showing frequent aberrant expression of non-melanocytic differentiation markers of different lineages, posing remarkable challenges due to several alternative differential diagnoses including undifferentiated carcinoma and sarcomas. When melanoma loses its typical morpho-phenotype by routinely used diagnostic immunohistochemical markers, it is defined as “dedifferentiated melanoma”. Historically, this process was closely related to diagnostic interpretative difficulties. In recent years, however, dedifferentiation has been increasingly recognized as an important biological phenomenon that demonstrates the phenotypic and genetic plasticity of melanoma, and specifically the non-irreversibility of the multistep cancerogenesis. Furthermore, dedifferentiation emerged as a general hallmark of cancer evolution and a common denominator of cross-resistance to both targeted and immunotherapy. In this review, we summarize the histopathological features, the genetic and epigenetic bases underlying the dedifferentiated phenotype in melanomas and provide additional support that dedifferentiation is a mechanism of resistance to immunotherapy and targeted therapy.